Reassessing the english course offered to computer engineering students at the national school of applied sciences of al-hoceima in morocco: an action research project. - Dahbi, M. (Africa Education Review, 2015)
In computer engineering education, specific English language practices are needed to enable computer engineering students to succeed in professional settings. This study was conducted for two purposes. First, it aimed at investigating to what extent the English courses offered to computer engineering students at the National School of Applied Sciences in Al-Hoceima were successful in fulfilling the job requirements of the prospective engineers. And the second objective was to devise an English for Specific Purposes (ESP) course that is rather related to the field of specialization of the respondents and attends to their communicative needs as well. For these purposes a ‘needs analysis questionnaire’ was devised to identify these students' perceptions of the English language practices used, the importance of these practices, the areas of language use that they need training/teaching in, and their preferences for the English language course. The results stressed the significance of English for computer engineering students. They also identified the students' lacks, needs and interests with regard to English language practices. The study concluded with pedagogical implications.